Rapid Implementation of Remote Online Patient Portal Activation in a Children's Hospital during the COVID-19 Pandemic - Vuong, Kim T.; Rungvivatjarus, Tiranun; Garcia, Isabel P.; Lewis, Cindy; Miller, Lisa; Kuelbs, Cynthia L. (ACI Open, 2021)
Background Patient portal access allows more patient engagement, yet portal usage is not universal. Telemedicine visits became critical when the coronavirus disease 2019 (COVID-19) pandemic limited in-office visits. Given physical distancing requirements and telemedicine platform integrated into the patient portal, our institution needed to rapidly enroll patients and their proxies remotely, including hospitalized patients, to minimize care disruptions.Objectives The study aimed to describe the rapid implementation of remote patient portal activation in a pediatric integrated delivery network during the COVID-19 pandemic. Additionally, to increase the percentage of patients with active portal status upon discharge by 15% (absolute change) across inpatient units within 3 months.Methods A multidisciplinary taskforce utilized quality improvement tools to identify barriers to successful inpatient patient portal activation followed by rapid intervention cycles to effect change. Weekly progress was monitored on a portal activation dashboard.Results We created clinical decision support tools and training within 2 weeks. Active patient portal status upon hospital discharge increased from 44 to 66% within 12 weeks. Online patient portal conversion within 7 days after hospital discharge increased from 6.0 to 24%. Offer rate increased from 73 to 85% across all inpatient units.Conclusion We rapidly and effectively implemented a remote proxy portal activation process in the inpatient setting. Remote activation, training, clinical decision support, multidisciplinary involvement, and emphasis on the portal as integral to ongoing care allowed us to dramatically increase portal conversion. This experience may be informative for pediatric hospitals aiming to increase proxy portal enrollment and adult hospitals with medical decision-making proxies.
Keywords: patient portal; telemedicine; pediatrics; patient engagement; patient provider communication